The Concept of Institutionalization of Islamic Education in Its Contribution to the Cultural Behavior of Society - Ravico, Ravico; Bahar, Mahdi; Karim, Maizar; Firman, Firman (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
This study is part of a dissertation on the history of Islamic education’s institutionalization and its contribution. This is due to the conclusion that Islamic education in a region ought to be able to alter the mentality and behavior of animist culture in a society. In actuality, however, people’s behavior is still cloaked in theatrics. Therefore, it is necessary to maintain the theme’s conception. This study employs qualitative research methods and a literature review approach, with the phases of reading, reviewing, and analyzing findings from online and offline libraries. This study provides the definition of Islamic educational institutions, which are educational systems that endeavor to modify behavior and thought in accordance with Islamic principles. Community Culture consists of the collective ideas and behaviors of the community that are rooted in the individual identities of its members.